Graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
By covering polyolefins and/or polyurethane on the surface of graphite particles to form a polymer film, the problem that existing graphite negative electrode materials are difficult to take into account low specific surface area and high compaction density is solved, and efficient and low-cost graphite negative electrode materials are achieved, thereby improving battery performance.
Patent Information
- Application Number
- CN202411581669.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-25
AI Technical Summary
The existing graphite anode materials are difficult to maintain high compaction density while reducing the specific surface area, and are costly.
By covering a small amount of polyolefin and/or polyurethane on the surface of graphite particles, forming a polymer film can not only reduce the specific surface area but also improve the compaction density.
The low specific surface area and high tap density of graphite negative electrode materials are achieved, which reduces production costs and improves the capacity of the battery and the first-time Coulomb efficiency.
Smart Images

Figure CN119517955A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a graphite negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art
[0002] After decades of development, graphite is still the main negative electrode material for lithium-ion batteries. With the development and progress of lithium-ion battery technology, graphite performance has entered a bottleneck period. The products of major negative electrode manufacturers are seriously homogenized, so reducing costs has become the top priority in the current research field of graphite negative electrode materials.
[0003] Resistor materials, waste graphite crucibles, graphite plates and other materials are auxiliary materials and equipment used in graphitization furnaces. These materials have undergone multiple graphitizations and have the properties of artificial graphite. Compared with coke as a raw material, using resistor materials, waste graphite crucibles, graphite plates and other materials as raw materials for artificial graphite can save the graphitization process, which is the most expensive process in artificial graphite. Therefore, using resistor materials, waste graphite crucibles, graphite plates and other materials as raw materials for artificial graphite can greatly reduce costs.
[0004] However, the graphite negative electrode currently made of materials such as resistors, discarded graphite crucibles and graphite plates has problems such as poor processing performance, low tap density, high specific surface area, and low first coulomb efficiency. Specifically, the prior art uses resistors, discarded graphite crucibles and graphite plates to prepare graphite negative electrodes in the following process: the crushing end is shaped to remove fine powder to improve tap density and processing performance, and then a large amount of asphalt or resin is coated for carbonization to reduce the specific surface area and improve the first coulomb efficiency. For example, patent CN115893402A discloses a method for preparing low-expansion high-rate graphite negative electrode materials from crucible waste, which reduces the specific surface area and improves the first coulomb efficiency by asphalt coating. However, the applicant of the present invention found that the conventional asphalt or resin coating carbonization process requires the addition of a large amount of asphalt or resin. If the amount used is small, the specific surface area cannot be effectively reduced. A large amount of asphalt or resin will penetrate into the graphite pores and form soft carbon or hard carbon after carbonization, which will hinder the movement of graphite sheets when rolling the electrode sheets, resulting in a significant reduction in the compaction density of the graphite negative electrode material, which limits the application scenarios.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a graphite negative electrode material, which can significantly reduce the specific surface area and increase the compaction density by coating a small amount of polyolefin and / or polyurethane on the surface of graphite particles, thereby solving the problem that the prior art adopts asphalt or resin coating carbonization process and cannot take into account both low specific surface area and high compaction.
[0007] The second object of the present invention is to provide a method for preparing a graphite negative electrode material, wherein the graphite negative electrode material prepared by the method has both high compaction density and low specific surface area, and the method is simple and easy to operate, has low energy consumption and low cost.
[0008] The third object of the present invention is to provide a negative electrode sheet having the advantages of high capacity and high first coulombic efficiency.
[0009] A fourth object of the present invention is to provide a lithium ion battery having the advantages of high capacity, high initial coulombic efficiency, and good cycle performance.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention first provides a graphite negative electrode material, including composite particles, wherein the composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, and the material of the polymer film includes polyolefin and / or polyurethane; the graphite negative electrode material is subjected to a thermal gravimetric test in an air atmosphere, and the weight loss ratio of the TG curve obtained between 200 and 600°C is 1% to 5%.
[0012] Furthermore, the polyolefin includes polyethylene and / or polypropylene.
[0013] Furthermore, the relative molecular mass of the polyolefin is 200,000 to 500,000, and the density is 0.92 to 0.95 g / cm 3 .
[0014] Furthermore, the DSC curve obtained by performing a DSC test on the graphite negative electrode material in an air atmosphere has an exothermic peak between 200 and 500°C.
[0015] Furthermore, the pore volume of the graphite negative electrode material is 0.025 to 0.035 cm 3 / g.
[0016] Furthermore, the tap density of the graphite negative electrode material is ≥0.8 g / cm 3 .
[0017] Furthermore, the graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is significantly different from the defect D peak attributable to the C atomic sp 2 The intensity of the hybrid in-plane stretching vibration G peak is higher than the average value I d / I g Satisfy 0.1≤I d / I g ≤0.2.
[0018] Furthermore, the graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is significantly different from the defect D peak attributable to the C atomic sp 2 The average value of the intensity ratio of the hybrid in-plane stretching vibration G peak is I d / I g , the data of the Raman scan test is pressed d / I g Arrange from largest to smallest, the 10th% of the total number of I d / I g Value is I d / I g 10, the 50% number of the total number of I d / I g Value is I d / I g 50, the 90th percentile of the total number of I d / I g Value is I d / I g 90,I d / I g Distribution width K90 = (I d / I g 90-I d / I g 10) / I d / I g 50, K90≤1.0.
[0019] Furthermore, the Dv00 particle size of the graphite negative electrode material is ≥1.0 μm.
[0020] Furthermore, the Dv50 particle size of the graphite negative electrode material is 10 to 23 μm.
[0021] Furthermore, the ash content of the graphite negative electrode material is ≤0.1%.
[0022] Furthermore, the specific surface area of the graphite negative electrode material is ≤3.0m 2 / g.
[0023] Furthermore, the specific surface area of the graphite negative electrode material is ≤2.1m 2 / g.
[0024] Furthermore, the powder compaction density of the graphite negative electrode material under a pressure of 5 tons is ≥1.80 g / cm 3 .
[0025] Furthermore, the powder compaction density of the graphite negative electrode material under a pressure of 5 tons is ≥1.90 g / cm 3 .
[0026] Furthermore, the graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles.
[0027] Furthermore, the specific surface area of the graphite particles is ≤15m 2 / g.
[0028] Furthermore, the ash content in the graphite particles is ≤0.1%, and the magnetic foreign matter content is ≤5ppm.
[0029] Furthermore, the capacity of the battery containing the graphite negative electrode material is ≥345 mAh / g.
[0030] Furthermore, the first coulombic efficiency of the battery containing the graphite negative electrode material is ≥88.0%.
[0031] The present invention further provides a method for preparing the graphite negative electrode material, comprising the following steps: mixing graphite particles with a polymer and heating them, melting the polymer into a liquid state and coating the surface of the graphite particles, and forming a polymer film after cooling to obtain the graphite negative electrode material.
[0032] Furthermore, the graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles.
[0033] Furthermore, the polymer includes polyolefin and / or polyurethane; wherein the polyolefin includes polyethylene and / or polypropylene.
[0034] Furthermore, the mass ratio of the graphite particles to the polymer is 93-99:1-7.
[0035] Furthermore, the heating temperature is 150-300°C.
[0036] Furthermore, the heating insulation time is 1 to 6 hours.
[0037] Furthermore, the heating rate of the heating is 1 to 10°C / min.
[0038] Furthermore, the waste resistor material particles, the waste insulation material particles, the waste graphite crucible particles, the waste graphite electrode particles and the waste graphite plate particles are crushed, shaped into a spheroidal shape and impurities are removed.
[0039] Furthermore, the Dv50 particle size of the material after the shaping and spheroidization treatment is 10-23 μm, and the specific surface area is ≤15m 2 / g.
[0040] Furthermore, the impurity removal method includes pickling and / or demagnetization.
[0041] Furthermore, the ash content of the material after impurities removal is ≤0.1%, and / or the content of magnetic foreign matter in the material after impurities removal is ≤5ppm.
[0042] Furthermore, the step of screening is also included after the cooling.
[0043] Furthermore, the mesh size of the sieve used for the screening is 200 to 600 meshes.
[0044] The present invention further provides a negative electrode sheet, comprising the graphite negative electrode material.
[0045] The present invention also provides a lithium ion battery, comprising the negative electrode sheet.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The graphite negative electrode material provided by the present invention can significantly reduce the specific surface area and increase the powder compaction density by coating a small amount of polyolefin and / or polyurethane on the surface of graphite particles.
[0048] (2) The graphite negative electrode material provided by the present invention and the polymer film can stabilize the SEI film, increase the initial coulombic efficiency, and improve the cycle performance.
[0049] (3) The graphite negative electrode material provided by the present invention can achieve the effect of effectively reducing the specific surface area when a relatively low amount of polymer is added.
[0050] (4) The graphite negative electrode material provided by the present invention has a high tap density.
[0051] (5) I of the graphite negative electrode material provided by the present invention d / I g Low, I d / I g The distribution K90 is low, that is, the polymer disorder is low and the polymer coating is uniform.
[0052] (6) The graphite negative electrode material provided by the present invention uses at least one of waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles, which can greatly reduce the production cost of the graphite negative electrode material and has the advantages of high capacity, high first coulombic efficiency and good cycle performance.
[0053] (7) The battery made using the graphite negative electrode material provided by the present invention has the advantages of high initial coulombic efficiency, high capacity, and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 A comparison diagram of the DSC curves of Example 1 and Comparative Example 1 provided by the present invention;
[0056] Figure 2 A comparison diagram of the DSC curves of Example 2 and Comparative Example 2 provided by the present invention;
[0057] Figure 3 This is a comparison diagram of the DSC curves of Example 3 and Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION
[0058] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0059] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0060] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0061] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0062] In a first aspect, the present invention provides a graphite negative electrode material, which includes composite particles, wherein the composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, and the material of the polymer film includes polyolefin and / or polyurethane.
[0063] The TG curve of the graphite negative electrode material obtained by the thermal gravimetric test in air atmosphere has a weight loss ratio of 1% to 5% between 200 and 600° C. It can be understood that the weight loss is caused by the thermal decomposition reaction of the polymer film, and the polymer reacts with oxygen to generate water and carbon dioxide.
[0064] The graphite negative electrode material provided by the present invention can significantly reduce the specific surface area and increase the powder compaction density by coating a small amount of polyolefin and / or polyurethane on the surface of graphite particles, thereby solving the problem that the prior art adopts asphalt or resin coating carbonization process and cannot achieve both low specific surface area and high compaction.
[0065] Among them, polyolefin and / or polyurethane are easy to form a film on the surface of graphite particles after heating, which can close the pores in the graphite particles, and high-density polymer macromolecules will hardly enter the pores, so the compaction density will not be reduced. Therefore, this application solves the problem that the traditional coating uses asphalt or resin to enter the pores of the material, resulting in the movement of the graphite sheet being hindered during the rolling of the pole piece, thereby greatly reducing the compaction density of the material.
[0066] In addition, polyolefins and polyurethanes have stable electrochemical properties and strong mechanical toughness. As polymer membranes, they can stabilize the SEI membrane, improve the first coulombic efficiency (abbreviated as first efficiency), and improve the cycle performance.
[0067] In some specific embodiments, the polyolefin includes polyethylene (PE) and / or polypropylene (PP). Polyethylene and polypropylene can form a film on the surface of graphite particles without entering the gaps, and polyethylene and polypropylene have very high electrochemical stability and strong mechanical toughness. Coating them on the surface of graphite particles to form a polymer film can stabilize the SEI film, improve the first coulomb efficiency (referred to as the first efficiency), and improve the cycle performance.
[0068] In some specific embodiments, the relative molecular mass of the polyolefin is 200,000 to 500,000, including but not limited to any one of 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, and 500,000, or a range between any two of them.
[0069] In some specific embodiments, the density of the polyolefin is 0.92 to 0.95 g / cm 3 , including but not limited to 0.92g / cm 3 , 0.93g / cm 3 、0.94g / cm3 , 0.95g / cm 3 .
[0070] In some specific embodiments, the DSC curve obtained by the DSC test of the graphite negative electrode material in an air atmosphere has an exothermic peak between 200 and 500°C (including but not limited to any point value of 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, and 500°C or the range value between any two thereof); the exothermic peak is the reaction peak of polymer pyrolysis, and the presence of the exothermic peak indicates that the polymer is successfully coated on the surface of the graphite particles.
[0071] In some specific embodiments, the pore volume of the graphite negative electrode material is 0.025 to 0.035 cm 3 / g, including but not limited to 0.025cm 3 / g, 0.026cm 3 / g, 0.028cm 3 / g, 0.03cm 3 / g, 0.032cm 3 / g, 0.033cm 3 / g, 0.035cm 3 The graphite negative electrode material provided by the present invention has a high pore volume because the polymer forms a polymer film on the surface of the graphite particles after the polymer is heated and melted, which closes the pores in the graphite particles and the polymer hardly enters the pores.
[0072] In some specific embodiments, the tap density of the graphite negative electrode material is ≥0.8 g / cm 3 ; Including but not limited to 0.82g / cm 3 、0.84g / cm 3 , 0.85g / cm 3 , 0.86g / cm 3 , 0.88g / cm 3 , 0.90g / cm 3 、0.92g / cm 3 , 0.93g / cm 3 、0.94g / cm 3 , 0.95g / cm 3 、0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 , 1g / cm 3 The graphite negative electrode material provided by the present invention has a high tap density.
[0073] In some specific embodiments, the graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is different from the defect D peak attributable to the C atomic sp 2 The intensity of the hybrid in-plane stretching vibration G peak is higher than the average value I d / I g Satisfy 0.1≤I d / I g ≤0.2; where I d / I g Including but not limited to any one of 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or any range between two of them. d / I g This indicates that the polymer has low disorder.
[0074] In some specific embodiments, the graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is different from the defect D peak attributable to the C atomic sp 2 The average value of the intensity ratio of the hybrid in-plane stretching vibration G peak is I d / I g , the data of the Raman scan test is pressed d / I g Arrange in descending order from largest to smallest, the 10% number of the total number d / I g Value is I d / I g 10, the 50% number of the total number of I d / I g Value is I d / I g 50, the 90th percentile of the total number of I d / I g Value is I d / I g 90 (For example, the number of points in the Raman scan test is 100. These 100 data are sorted in descending order from large to small, and the Id / Ig values of the 10th point, the 50th point, and the 90th point are selected, that is, I d / I g 10.I d / I g 50.I d / I g 90), I d / I g Distribution width K90 = (I d / I g 90-I d / I g 10) / I d / I g 50, K90≤1.0, the value of K90 includes but is not limited to any point value of 0.95, 0.9, 0.88, 0.86, 0.85, 0.83, 0.82, 0.8, 0.78, 0.76, 0.73, 0.7, 0.65, 0.6 or any range value between two of them. d / I g The distribution K90 is low, which indicates uniform polymer coating.
[0075] In some specific embodiments, the Dv00 particle size of the graphite negative electrode material is ≥ 1.0 μm, including but not limited to any point value of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 5.5 μm, and 5.8 μm, or a range value between any two of them. The Dv00 particle size refers to the particle size of the smallest particle when the particle size is arranged from small to large in terms of volume.
[0076] In some specific embodiments, the Dv50 particle size of the graphite negative electrode material is 10 to 23 μm, including but not limited to any point value of 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, and 23 μm, or a range value between any two of them.
[0077] In some specific embodiments, the ash content of the graphite negative electrode material is ≤ 0.1%, including but not limited to any point value of 0.08%, 0.06%, 0.05%, 0.03%, 0.01%, or any range value between two of them. The graphite negative electrode material provided by the present invention has low ash content, high capacity, low self-discharge, and good storage performance.
[0078] In some specific embodiments, the specific surface area of the graphite negative electrode material is ≤3.0 m 2 / g; including but not limited to 2.9m 2 / g, 2.8m 2 / g, 2.6m 2 / g, 2.5m 2 / g, 2.4m 2 / g, 2.3m 2 / g, 2.2m 2 / g, 2.1m 2 / g, 2.0m 2 / g, 1.9m 2 / g, 1.8m 2 / g, 1.7m 2 / g, 1.6m 2 / g, or a range of values between them.
[0079] In some specific embodiments, the specific surface area of the graphite negative electrode material is ≤2.1m 2 / g.
[0080] In some specific embodiments, the powder compaction density of the graphite negative electrode material under a pressure of 5 tons is ≥1.80 g / cm 3 ; Including but not limited to 1.85g / cm 3 , 1.9g / cm 3 、1.91g / cm 3 、1.92g / cm 3 , 1.93g / cm 3 , 1.94g / cm 3 , 1.95g / cm 3 , 1.96g / cm 3 , 1.97g / cm 3 、1.98g / cm 3 , 1.99g / cm 3 , 2g / cm 3 Any point value in or any range of values between them.
[0081] In some specific embodiments, the powder compaction density of the graphite negative electrode material under a pressure of 5 tons is ≥1.90 g / cm 3 .
[0082] In some specific embodiments, the graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles.
[0083] Among them, waste resistor particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles are auxiliary materials or utensils used in graphitization furnaces. These materials have undergone multiple graphitization and have the properties of artificial graphite.
[0084] At least one of waste resistor particles, waste insulation particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles is preferably used, which can greatly reduce the production cost of graphite negative electrode materials. In addition, the graphite negative electrode material provided by the present invention also has the advantages of good processing performance, high tap density, high powder compaction density, low specific surface area, high first coulomb efficiency, high capacity, etc.
[0085] In some specific embodiments, the specific surface area of the graphite particles is ≤15m 2 / g, including but not limited to 14m 2 / g, 13m 2 / g, 12m 2 / g, 11m 2 / g, 10m 2 / g, 9m 2 / g, 8m 2 / g, 7m 2 / g, 6m 2 / g, 5m 2 / g or any point value or range value between any two of them. The specific surface area of the graphite particles before coating is relatively high. The present invention can effectively reduce the specific surface area of the material after coating a specific type of polymer. The problem of high specific surface area of graphite materials made from waste materials is solved.
[0086] In some specific embodiments, the ash content (mass fraction) in the graphite particles is
[0087] ≤0.1%, including but not limited to any one of 0.08%, 0.06%, 0.05%, 0.03%, 0.01% or any range between them; the content of magnetic foreign matter (mainly including iron (Fe), chromium (Cr), nickel (Ni), zinc (Zn)) in the graphite particles is ≤5ppm, including but not limited to any one of 4ppm, 3ppm, 2ppm, 1ppm or any range between them. By controlling the ash content and magnetic foreign matter content in the graphite particles, self-discharge can be reduced and safety can be enhanced.
[0088] In some specific embodiments, the capacity of the battery containing the graphite negative electrode material is ≥345mAh / g; including but not limited to any one of 346mAh / g, 348mAh / g, 350mAh / g, 352mAh / g, 353mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 358mAh / g, 340mAh / g or the range value between any two of them.
[0089] In some specific embodiments, the first coulombic efficiency of the battery containing the graphite negative electrode material is ≥88.0%, including but not limited to 89%, 90%, 90.3%, 90.6%, 91%, 91.3%, 91.5%, 91.7%, 92%, 93%, 95%, any one of the point values or the range value between any two of them.
[0090] In a second aspect, the present invention provides a method for preparing the graphite negative electrode material, comprising the following steps: mixing graphite particles with a polymer and heating them to melt the polymer into a liquid state and coat the surface of the graphite particles, and forming a polymer film after cooling to obtain the graphite negative electrode material.
[0091] Under heating conditions, graphite particles are mixed with molten liquid polymers, and the liquid polymers can be coated on the surface of the graphite particles, and a polymer film is formed after cooling. It can be understood that the coating process is not a carbonization process.
[0092] Compared with the traditional method of high-temperature carbonization using asphalt or resin, the preparation method of the graphite negative electrode material provided by the present invention enables the molten liquid polymer to be coated on the surface of the graphite particles, and the obtained graphite negative electrode material has the effects of high compaction and low specific surface area.
[0093] Moreover, the method is simple to operate, suitable for mass production, and has low energy consumption and low cost.
[0094] In some specific embodiments, the graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles.
[0095] In some specific embodiments, the polymer includes polyolefin and / or polyurethane; wherein the polyolefin includes polyethylene and / or polypropylene.
[0096] In some specific embodiments, the mass ratio of the graphite particles to the polymer is 93-99:1-7, including but not limited to any point value of 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, 99:1 or a range value between any two of them.
[0097] In some specific embodiments, the heating temperature is 150-300° C., including but not limited to any point value of 150° C., 160° C., 180° C., 200° C., 230° C., 250° C., 280° C., 300° C., or any range value between two of them. Within this temperature range, the polymer can be melted into a liquid state but will not be carbonized.
[0098] In some specific embodiments, the heating holding time is 1 to 6 hours, including but not limited to any point value of 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, and 6 hours, or a range value between any two of them. That is, the mixing time of the graphite particles and the polymer is 1 to 6 hours. This ensures that the molten polymer is evenly coated on the surface of the graphite particles.
[0099] In some specific embodiments, the heating rate is 1-10°C / min, including but not limited to any one of 1°C / min, 2°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, or a range between any two of them.
[0100] In some specific implementations, the equipment used for the heating may be, for example, a drum furnace, a horizontal kettle, a VC heating furnace, etc., but is not limited thereto.
[0101] In some specific embodiments, the heating is performed under an inert atmosphere.
[0102] In some specific implementations, the waste resistor material particles, the waste insulation material particles, the waste graphite crucible particles, the waste graphite electrode particles and the waste graphite plate particles are crushed, shaped into a spheroidized state and impurities are removed.
[0103] Preferably, the pulverizing method comprises: firstly using a jaw crusher for coarse pulverization, and then using a roller mill or a mechanical mill for fine pulverization.
[0104] Preferably, the Dv00 particle size of the material after the shaping and spheroidization treatment is ≥1.0μm, including but not limited to any one of 1μm, 2μm, 3μm, 4μm, 5μm or any range between two of them; the Dv50 particle size of the material after the shaping and spheroidization treatment is 10-23μm, including but not limited to any one of 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 18μm, 20μm, 22μm, 23μm or any range between two of them; the tap density of the material after the shaping and spheroidization treatment is ≥0.8g / cm 3 , including but not limited to 0.82g / cm 3 、0.84g / cm 3 , 0.85g / cm 3 , 0.86g / cm 3 , 0.88g / cm 3 , 0.90g / cm 3 、0.92g / cm 3 , 0.93g / cm 3 、0.94g / cm 3 , 0.95g / cm 3 、0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 , 1g / cm 3 Any point value or range value between any two of the above; The specific surface area of the material after the shaping and spheroidization treatment is ≤15m 2 / g, including but not limited to 14m 2 / g, 13m 2 / g, 12m 2 / g, 11m 2 / g, 10m2 / g, 9m 2 / g, 8m 2 / g, 7m 2 / g, 6m 2 / g, 5m 2 / g or any point value or range value between any two; the powder compaction density of the material after the shaping and spheroidization treatment under a pressure of 5 tons is ≥1.80g / cm 3 , including but not limited to 1.85g / cm 3 , 1.9g / cm 3 、1.91g / cm 3 、1.92g / cm 3 , 1.93g / cm 3 , 1.94g / cm 3 , 1.95g / cm 3 , 1.96g / cm 3 , 1.97g / cm 3 、1.98g / cm 3 , 1.99g / cm 3 , 2g / cm 3 Any point value in or any range of values between them.
[0105] Preferably, the impurity removal method includes pickling and / or demagnetization, wherein pickling and / or demagnetization can remove impurities such as ash and magnetic foreign matter.
[0106] Preferably, the ash content of the material after impurities removal is ≤0.1%, including but not limited to any one of 0.08%, 0.06%, 0.05%, 0.03%, 0.01% or a range between any two of them; the magnetic foreign matter content is ≤5ppm, including but not limited to any one of 4ppm, 3ppm, 2ppm, 1ppm or a range between any two of them.
[0107] In some specific embodiments, the cooling further includes the steps of dispersion and screening; preferably, the mesh size of the sieve used for screening is 200-600 mesh, including but not limited to any point value of 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh or the range value between any two of them.
[0108] In some specific embodiments, the purpose of the dispersion is to break up and disperse uniformly. The equipment used for the dispersion can be, for example, a VC mixer, a zero-gravity mixer, a spiral mixer, etc., but is not limited thereto.
[0109] In some specific embodiments, the equipment used for the screening may be, for example, a vibrating screen and an ultrasonic vibrating screen, but is not limited thereto.
[0110] In a third aspect, the present invention provides a negative electrode sheet comprising the graphite negative electrode material.
[0111] The negative electrode sheet provided by the present invention has the advantages of high capacity, high initial efficiency, etc.
[0112] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the negative electrode sheet.
[0113] The lithium-ion battery has excellent electrochemical properties, especially high capacity and high initial efficiency.
[0114] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0115] Example 1
[0116] The method for preparing the graphite negative electrode material provided in this embodiment comprises the following steps:
[0117] The 2cm waste resistor material was crushed by roller mill to obtain a powder with a particle size of Dv50 = 10μm, and then shaped and spheroidized by a shaping machine to remove fine powder, and a shaped material with a particle size of Dv50 = 11μm was obtained, and its specific surface area is 11.9m 2 / g; demagnetize the shaped material and control the magnetic foreign matter to 0.2ppm.
[0118] The demagnetized graphite particles and PP were mixed evenly in a mass ratio of 93:7 using a VC mixer, and then loaded into a VC heating kettle. 2 The polymer was heated in the atmosphere to melt into liquid and coated on the surface of graphite particles, wherein the heating rate was 3°C / min, the temperature was raised to 180°C, the temperature was kept for 6 hours, and then cooled. The cooled material was dispersed and mixed by a high-speed disperser, and then sieved with a 325-mesh screen to obtain a low-cost graphite negative electrode material.
[0119] The graphite negative electrode material prepared in this embodiment includes composite particles, the composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, and the material of the polymer film includes polypropylene.
[0120] The specific surface area, powder compaction density under 5 tons pressure, pore volume, tap density, Dv00 particle size, Dv50 particle size, ash content, and conductivity of the graphite negative electrode material prepared in this embodiment were tested, and the results are shown in Table 1. The graphite negative electrode material prepared in this embodiment was subjected to TG test, DSC test, and Raman surface scanning test in air atmosphere to determine whether there is an exothermic peak between 200 and 500°C in the DSC curve, and to obtain the weight loss ratio, I d / I g and K90, the results are shown in Table 2 and Figure 1 shown.
[0121] Example 2
[0122] The method for preparing the graphite negative electrode material provided in this embodiment comprises the following steps:
[0123] The discarded graphite crucible was crushed by a jaw crusher and a roller mill to obtain a powder with a particle size of Dv50 = 15 μm, and then shaped and spheroidized by a shaping machine to remove fine powder, and a shaped material with a particle size of Dv50 = 16 μm was obtained, and its specific surface area is 9.4 m 2 / g; the shaped material is pickled and the magnetic foreign matter is controlled at 0.6ppm.
[0124] The acid-washed graphite particles and PE were mixed in a VC mixer at a mass ratio of 93:4, and then loaded into a VC heating kettle. 2 The polymer was heated in the atmosphere to melt into a liquid state and coated on the surface of the graphite particles, wherein the heating rate was 5°C / min, the temperature was raised to 250°C, the temperature was kept for 3 hours, and then cooled. The cooled material was dispersed and mixed by a high-speed disperser, and then sieved with a 325-mesh screen to obtain a low-cost graphite negative electrode material.
[0125] The graphite negative electrode material prepared in this embodiment includes composite particles, the composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, and the material of the polymer film includes polyethylene.
[0126] The specific surface area, powder compaction density under 5 tons pressure, pore volume, tap density, Dv00 particle size, Dv50 particle size, ash content, and conductivity of the graphite negative electrode material prepared in this embodiment were tested, and the results are shown in Table 1. The graphite negative electrode material prepared in this embodiment was subjected to TG test, DSC test, and Raman surface scanning test in air atmosphere to determine whether there is an exothermic peak between 200 and 500°C in the DSC curve, and to obtain the weight loss ratio, I d / I g and K90, the results are shown in Table 2 and Figure 2 shown.
[0127] Example 3
[0128] The method for preparing the graphite negative electrode material provided in this embodiment comprises the following steps:
[0129] The waste graphite plate was crushed by jaw crusher and roller mill to obtain powder with Dv50 particle size = 20μm, and then shaped and spheroidized by shaping machine to remove fine powder, and the shaped material with Dv50 particle size = 21μm was obtained, and its specific surface area is 6.8m 2 / g; the shaped material is pickled and the magnetic foreign matter is controlled at 0.8ppm.
[0130] The acid-washed graphite particles and polyurethane resin were mixed in a mass ratio of 99:1 using a VC mixer, and then loaded into a VC heating kettle. 2 The polymer is heated in the atmosphere to melt into a liquid state and coat the surface of the graphite particles, wherein the heating rate is 5°C / min, the temperature is raised to 250°C, the temperature is kept for 1 hour, and then cooled. The cooled material is dispersed and mixed by a high-speed disperser, and then sieved with a 325-mesh screen to obtain a low-cost graphite negative electrode material.
[0131] The graphite negative electrode material prepared in this embodiment includes composite particles, the composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, and the material of the polymer film includes polyurethane.
[0132] The specific surface area, powder compaction density under 5 tons pressure, pore volume, tap density, Dv00 particle size, Dv50 particle size, ash content, and conductivity of the graphite negative electrode material prepared in this embodiment were tested, and the results are shown in Table 1. The graphite negative electrode material prepared in this embodiment was subjected to TG test, DSC test, and Raman surface scanning test in air atmosphere to determine whether there is an exothermic peak between 200 and 500°C in the DSC curve, and to obtain the weight loss ratio, I d / I g and K90, the results are shown in Table 2 and Figure 3 shown.
[0133] Example 4
[0134] The preparation method of the graphite negative electrode material provided in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of the demagnetized graphite particles and PP is replaced with 96:4.
[0135] Example 5
[0136] The preparation method of the graphite negative electrode material provided in this embodiment is basically the same as that in embodiment 1, except that artificial graphite particles with a Dv50 particle size of 11 μm are used, and the specific surface area is 1.92 m 2 / g, demagnetize it and control the magnetic foreign matter to 0.5ppm.
[0137] Comparative Example 1
[0138] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that PP is replaced with an equal mass of asphalt, and heating is replaced with carbonization. The specific steps are: the demagnetized graphite particles and asphalt are mixed in a mass ratio of 93:7, then loaded into a sagger, placed in a roller kiln at 1150°C for carbonization for 15 hours, and then cooled.
[0139] Comparative Example 2
[0140] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that in Example 2, except that PP is replaced with an equal mass of asphalt, and heating is replaced with carbonization. The specific steps are: the acid-washed graphite particles and asphalt are mixed in a mass ratio of 93:4, then loaded into a sagger, placed in a roller kiln at 1150°C for carbonization for 15 hours, and then cooled.
[0141] Comparative Example 3
[0142] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that in Example 2, except that PP is replaced with asphalt, the amount of asphalt is adjusted, and heating is replaced with carbonization. The specific steps are: the acid-washed graphite particles and asphalt are mixed in a mass ratio of 98:2, then loaded into a sagger, placed in a roller kiln at 1150°C for carbonization for 15 hours, and then cooled.
[0143] Comparative Example 4
[0144] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that PP is replaced by polyurethane resin, and heating is replaced by carbonization. The specific steps are: the demagnetized graphite particles and the above-mentioned resin are mixed in a mass ratio of 93:7, then loaded into a sagger, placed in a roller kiln at 1150°C for carbonization for 15 hours, and then cooled.
[0145] Comparative Example 5
[0146] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that in Example 1, except that PP is replaced with asphalt of the same mass.
[0147] Comparative Example 6
[0148] The preparation method of the graphite negative electrode material provided in this comparative example is basically the same as that of Example 1, except that no asphalt is added (ie, no polymer film).
[0149] The specific surface area, powder compaction density under 5 tons of pressure (referred to as 5 tons of powder compaction), pore volume, tap density, Dv00 particle size, Dv50 particle size, ash content and conductivity of the graphite negative electrode materials prepared in Comparative Examples 1 to 3 are shown in Table 1.
[0150] The graphite negative electrode materials prepared in Comparative Examples 1 to 3 were subjected to TG test, DSC test and Raman scan test in air atmosphere to determine whether there was an exothermic peak between 200 and 500 ° C in the DSC curve, and to obtain the weight loss ratio, I d / I g and I d / I g Distribution width K90, the results are shown in Table 2.
[0151] Specific surface area test method: Quantachrome nitrogen adsorption-desorption method.
[0152] Pore volume test method: Micromeritics physical adsorption instrument test.
[0153] Powder compaction density test method under 5 tons pressure: automatic powder compactor test.
[0154] Tap density test method: vibrate the tap density meter 3000 times.
[0155] Particle size test method: Malvern 3000 test.
[0156] Ash content test method: muffle furnace at 800℃ for 8 hours.
[0157] Raman spectroscopy test method: Raman surface scan 400 points.
[0158] Test method for TG test and DSC test in air atmosphere: air atmosphere, room temperature -1000°C, 5°C / min.
[0159] Table 1 Physical and chemical indicators of graphite negative electrode materials
[0160]
[0161] Table 2 TG test and DSC test results of graphite negative electrode materials
[0162]
[0163] Furthermore, button-type batteries were assembled using the graphite negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 as negative electrode active materials, and the capacity and first efficiency tests were performed on each battery. The results are shown in Table 3.
[0164] Table 3 Electrochemical performance test results of batteries assembled with graphite negative electrode materials
[0165] Group Capacity (mAh / g) First effect (%) Example 1 354.6 90.3 Example 2 353.8 91.7 Example 3 354.2 91.3 Comparative Example 1 352.6 80.8 Comparative Example 2 350.4 89.1 Comparative Example 3 351.3 88.4
[0166] Referring to the test results of Table 1, Table 2 and Table 3, by comparing Example 1 with Comparative Example 1, and Example 2 with Comparative Example 2, it can be seen that when the coating material is of the same quality, the polymer coating has a lower specific surface area than the graphite negative electrode material obtained by the asphalt or resin carbonization process, a higher powder compaction density, a higher tap density, a higher compaction density, a higher capacity, and a higher first efficiency. By comparing Example 3 with Comparative Example 3, it can be seen that even if the amount of asphalt used in Comparative Example 3 is increased, the specific surface area cannot be effectively reduced.
[0167] Compared with the Raman surface scan of the graphite negative electrode material obtained by coating graphite with asphalt in each comparative example, d / I g Average value, Raman scan of graphite negative electrode material obtained in each embodiment d / I g The average value is lower, which indicates that the disorder degree of each embodiment after polymer coating is lower. At the same time, compared with the graphite negative electrode material obtained by asphalt coating graphite in each comparative example, the I d / I g The distribution width K90, the K90 of the graphite negative electrode material obtained in each embodiment is lower, which shows that the polymer coating in each embodiment is more uniform. However, in Comparative Examples 1 to 3, the soft carbon or hard carbon formed by carbonization of asphalt is mostly distributed in the pores, and the soft carbon or hard carbon on the outer surface of the graphite is unevenly distributed.
[0168] Moreover, the pore volumes of Comparative Examples 1 to 3 are lower, which indicates that the asphalt coating will block the pores of the graphite and form soft carbon inside the pores. Since the soft carbon has a low compaction density and penetrates into the pores, it hinders the movement of the graphite sheets when the electrode sheets are rolled. As a result, the compaction density of the graphite negative electrode materials of Comparative Examples 1 to 3 is also low.
[0169] Figure 1 A comparison diagram of the DSC curves of Example 1 and Comparative Example 1 provided by the present invention; Figure 2 A comparison diagram of the DSC curves of Example 2 and Comparative Example 2 provided by the present invention; Figure 3 This is a comparison diagram of the DSC curves of Example 3 and Comparative Example 3 provided by the present invention. Figure 1 to Figure 3 It can be seen that in the DSC curves of Examples 1 to 3, there is a small exothermic peak between 200 and 500°C, which is the reaction peak of the polymer. However, in Comparative Examples 1 to 3, which are coated with asphalt, there is no peak between 200 and 500°C.
[0170] In summary, the graphite negative electrode material provided by the present invention can seal the pores in the graphite by coating a layer of polymer film on the surface of the graphite particles. Unlike the traditional asphalt and resin coating, which fills the pores with carbon and requires more coating auxiliary materials to reduce the specific surface area, resulting in low compaction of the coated graphite negative electrode. The graphite negative electrode material provided by the present invention can reduce the specific surface area of the graphite negative electrode material by adding a small amount of polymer, and at the same time, the compaction density and tap density of the coated graphite negative electrode material are high. In addition, the polymer film has stable electrochemical properties and strong mechanical toughness, can stabilize the SEI film, improve the first coulomb efficiency, and improve the cycle performance.
[0171] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A graphite negative electrode material, characterized in that: The composite particles include graphite particles and a polymer film coated on the surface of the graphite particles, wherein the material of the polymer film includes polyolefin and / or polyurethane; The graphite negative electrode material is subjected to a thermal gravimetric test in an air atmosphere, and the weight loss ratio of the TG curve obtained between 200 and 600° C. is 1% to 5%.
2. The graphite negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The polyolefin comprises polyethylene and / or polypropylene; (2) The relative molecular mass of the polyolefin is 200,000 to 500,000, and the density is 0.92 to 0.95 g / cm 3 .
3. The graphite negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The DSC curve obtained by DSC testing of the graphite negative electrode material in air atmosphere has an exothermic peak between 200 and 500° C.; (2) The pore volume of the graphite negative electrode material is 0.025 to 0.035 cm 3 / g; (3) The tap density of the graphite negative electrode material is ≥ 0.8 g / cm 3 ; (4) The graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is different from the defect D peak attributable to the C atomic sp 2 The intensity of the hybrid in-plane stretching vibration G peak is higher than the average value I d / I g Satisfy 0.1≤I d / I g ≤0.2; (5) The graphite negative electrode material is subjected to Raman scanning test, and the defect D peak attributable to the C atomic lattice is different from the defect D peak attributable to the C atomic sp 2 The average value of the intensity ratio of the hybrid in-plane stretching vibration G peak is I d / I g , the data of the Raman scan test is pressed d / I g Arrange from largest to smallest, the 10th% of the total number of I d / I g Value is I d / I g 10, the 50% number of the total number of I d / I g Value is I d / I g 50, the 90th percentile of the total number of I d / I g Value is I d / I g 90,I d / I g Distribution width K90 = (I d / I g 90-I d / I g 10) / I d / I g 50, K90≤1.
0.
4. The graphite negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The Dv00 particle size of the graphite negative electrode material is ≥1.0 μm; (2) The Dv50 particle size of the graphite negative electrode material is 10 to 23 μm; (3) The ash content of the graphite negative electrode material is ≤0.1%; (4) The specific surface area of the graphite negative electrode material is ≤3.0m 2 / g; (5) The specific surface area of the graphite negative electrode material is ≤2.1m 2 / g; (6) The powder compaction density of the graphite negative electrode material under 5 tons of pressure is ≥1.80g / cm 3 ; (7) The powder compaction density of the graphite negative electrode material under 5 tons of pressure is ≥1.90g / cm 3 .
5. The graphite negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles; (2) The specific surface area of the graphite particles is ≤15m 2 / g; (3) The ash content in the graphite particles is ≤0.1%, and the magnetic foreign matter content is ≤5ppm.
6. The graphite negative electrode material according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: (1) The capacity of the battery containing the graphite negative electrode material is ≥345 mAh / g; (2) The first coulombic efficiency of a battery containing the graphite negative electrode material is ≥88.0%.
7. The method for preparing the graphite negative electrode material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing graphite particles and polymers and heating them, so that the polymers are melted into liquid and coated on the surfaces of the graphite particles, and cooling them to form polymer films, thereby obtaining the graphite negative electrode material.
8. The method for preparing the graphite negative electrode material according to claim 7, characterized in that: At least one of the following conditions is met: (1) The graphite particles include at least one of artificial graphite particles, natural graphite particles, waste resistor material particles, waste insulation material particles, waste graphite crucible particles, waste graphite electrode particles and waste graphite plate particles; (2) The polymer comprises polyolefin and / or polyurethane; wherein the polyolefin comprises polyethylene and / or polypropylene; (3) The mass ratio of the graphite particles to the polymer is 93-99:1-7; (4) The heating temperature is 150 to 300° C.; (5) The heating holding time is 1 to 6 hours; (6) The heating rate is 1 to 10°C / min; (7) The waste resistor material particles, the waste insulation material particles, the waste graphite crucible particles, the waste graphite electrode particles and the waste graphite plate particles are crushed, shaped and spheroidized and impurities are removed; preferably, the Dv50 particle size of the material after the shaping and spheroidization treatment is 10 to 23 μm, and the specific surface area is ≤15m 2 / g; preferably, the impurity removal method includes pickling and / or demagnetization; preferably, the ash content of the material after impurity removal is ≤0.1%, and / or the content of magnetic foreign matter in the material after impurity removal is ≤5ppm; (8) After the cooling, a screening step is also included; preferably, the mesh size of the sieve used for the screening is 200 to 600 meshes.
9. A negative electrode sheet, characterized in that: Comprising the graphite negative electrode material as claimed in any one of claims 1 to 6.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Negative electrode material, preparation method thereof and battery
CN122370372A